Worst-case portfolio optimization under stochastic interest rate risk - Tina Engler; Ralf Korn (Risks, 2014)
We investigate a portfolio optimization problem under the threat of a market crash, where the interest rate of the bond is modeled as a Vasicek process, which is correlated with the stock price process. We adopt a non-probabilistic worst-case approach for the height and time of the market crash. On a given time horizon [0; T], we then maximize the investor's expected utility of terminal wealth in the worst-case crash scenario. Our main result is an explicit characterization of the worst-case optimal portfolio strategy for the class of HARA (hyperbolic absolute risk aversion) utility functions.
Keywords: 330; portfolio optimization; worst-case optimization; stochastic interest rate